Analysis of the Role of Key Actors (Public and Private) in the Regeneration of Urban Neighborhoods (Case Study: Sarab Neighborhood of Mashhad) - Zohreh Fanni; Nasim Niknami; Sajad Saeedi (علوم محیطی)
Introduction: One of the most significant and complex social transformations in the world over the past half-century has been urbanization, which has led to changes in the physical and economic structure of cities and has increasingly highlighted the importance of revitalizing dilapidated and inefficient urban fabrics. Urban regeneration utilizes the existing potentials in dilapidated areas and the extensive participation of public and private institutions with the least possible budget to restore social life and economic prosperity to the urban fabric. Material and Methods: This research is applied in terms of purpose and descriptive-analytical in terms of method. The method of data collection is based on library resources and questionnaires. The statistical population of this research includes experts and elites in the field of urban planning. To identify and formulate regeneration strategies for urban neighborhoods, the SWOT model was used. To rank the output strategies of the model, the QSPM model was used in the framework of internal and external position evaluation. After analyzing the information, a futures research questionnaire was prepared and after being answered by the experts, the Mactor software was used to identify the key actors and their roles in relation to the mentioned strategies. Results and Discussion: The research findings showed six strategies in a defensive mode in order of priority. In the analysis of the behavior of key actors towards the mentioned strategies, the role of the municipality, including planning, institution building, financing and implementation, and quasi-governmental organizations with the most impact, of which the Astan Qods and the Oqaf have been the most key and influential actors in the various social, economic, cultural, political and spatial-physical fields. In the following, the level of insistence of the actors (their agreement) with the mentioned strategies in the field of neighborhood regeneration showed that the actors have the most insistence on strategies such as using the location of the neighborhood in terms of access and building prices to create new jobs and use of fallow and abandoned lands to respond to the neighborhood's shortages, especially green spaces. The least of which was the use of an educated, young, and specialized population of the neighborhood in planning and revitalizing the neighborhood and paying more attention to the permeability of the neighborhood through the organization of the street network. Also, according to the distance between the actors, which showed their level of convergence, it can be mentioned that the municipality, quasi-governmental organizations (Astan Qods, Oqaf, etc.) and the Urban Renewal and Development Organization have a significant convergence with each other. Conclusion: With the cooperation and close communication between municipalities as the main axis of executive actions in urban management and quasi-governmental organizations, including the Astan Qods and the Oqaf, it is possible to witness the acceleration of the regeneration of inefficient and dilapidated urban fabrics. In addition, the insistence of the actors on the location of the Sarab neighborhood in Mashhad city in terms of access and building prices to create new jobs emphasizes the importance of the economic aspect in the actions of the actors about regeneration measures to achieve their ultimate goals alongside the use of existing potentials. In this regard, the convergence of the municipality, quasi-governmental organizations (Astan Qods, Oqaf, etc.) and the Urban Renewal and Development Organization indicate a relative consensus and greater overlap between them regarding the envisaged future for the strategies mentioned.